Research and application of numerical models of typhoon surges in China Seas (MAUSAM, 1997)
In this paper, three numerical models of typhoon surge are discussed briefly. The first one is called Five-basin Model (FbM). The second one is called SLOSH (Sea, Lake and Overland Surges from Hurricanes), 5 SLOSH-type basins covering the entire China coastlines were developed in a joint project between authors and Jelesnianski et al. (1992) of U.S.A. The two models have been used in real-time forecasting of typhoon surge. The third one is a new developing model in which inundation using the scheme originated by Flather and Heaps (1975) and astronomical used was included. A multiple nested grid system was developed.